(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث التعرف على مشكلات تدريس مادة العلوم للطلبة المعاقين سمعياً في مرحلة التعليم الأساسي من وجهة نظر معلميهم ، وتمثلت مشكلة البحث بالسؤال الرئيس التالي : ما المشكلات التي تواجه تدريس مادة العلوم للطلبة الصم في مرحلة التعليم الأساسي من وجهة نظر معلميهم وفق المحاور الآتية : محتوى الكتاب وشكله، طرائق التدريس وأساليب التواصل، وسائل التدريس وتقنياته، المعلم وواقعه المهني، التقويم وأدواته ؟ تكونت عينة البحث من مجتمع الدراسة كامل (60) معلمة من معلمي الصم. ولتحقيق هدف البحث صممت الباحثة مقياس مؤلف من (123) فقرة ذا تدرج ثلاثي للإجابة(موافق، لا أدري، غير موافق)، وتم توزيعه على أفراد عينة البحث. وأظهرت النتائج وجود مجموعة مشكلات أهمها :أن حجم الكتاب وعدد صفحاته غير مناسب للتلاميذ المعاقين سمعياً، وأن الصور المستخدمة في الكتاب وألوانها غير جذابة وغير مشوقة للتلاميذ المعاقين سمعياً، واعتماد المعلم على الطريقة الإلقائية في تعليم الصم لاعتقاده أنها الطريقة الوحيدة المناسبة للتلاميذ الصم، وعدم إدراك المعلم لأهمية الأنشطة الإضافية أو لأهمية مشاركة التلاميذ بالتجارب العلمية. وعدم توافر أفلام تعليمية تتناسب مع محتوى الكتاب المدرسي في المدرسة، وعدم استعانة المعلم بالتقانات التعليمية الحديثة كالحاسوب في توضيح المادة العلمية التي يدرسها. وعدم رغبة أغلب أفراد عينة البحث بالعمل مع الطلاب الصم ، وعدم كفاية الأسلوب الحالي للاختبارات الكتابية لتقويم التلاميذ الصم بشكل صحيح في مادة العلوم. وقد خلص البحث إلى التوصيات التالية : 1- إعادة تعديل كتاب العلوم من قبل أخصائيين تربويين وأخصائيين تربية خاصة. 2- إشراف وزارة التربية على معهد التربية الخاصة للصم بشكل مباشر . 3- إخضاع المعلمين لدورات تدريبية مستمرة ومتنوعة لمساعدتهم على تطوير إمكاناتهم ومعرفتهم للتعرف على طرائق تدريس المعاقين سمعياً وأساليب التواصل المثلى معهم . The research aims at identifying the problems of teaching science to students with disabilities in the audio stage of basic education According to teachers, the problem has been research to question the President the following: What are the problems facing the teaching of science for students of the Deaf in the stage of basic education from the viewpoint of teachers, according to the following themes: the book’s contents and form of teaching methods and modes of communication, teaching methods and techniques, the teacher and the reality of vocational Calendar and tools? The sample consists of the entire study population (60) of the teachers of the deaf. To achieve the objective of this research, researchers designed a scale consisting of (123) include a three-paragraph for the answer (OK, I do not know, but OK), was distributed to members of the research sample. The results showed the existence of problems, including: the size of the book and the number of pages unsuitable for hearing-impaired children. The images and colors used in the book are not attractive and interesting for students with acoustic disabilities, and the adoption of the teacher on the way Aliquippa in the education of the deaf because he thought it the only appropriate way for students, deaf and lack of awareness Teacher of the importance of additional activities or the importance of the participation of students’ scientific experiments. And the lack of educational films commensurate with the content of the textbook at school, and not to use the teacher Blatant modern educational computer literate to clarify the scientific material to be considered. And the unwillingness of most members of the research sample to work with deaf students, and the inadequacy of the current method of written tests to assess correctly the deaf students in the sciences. The research concluded the following recommendations: 1 - re-adjust science book by education specialists and special education specialists. 2 - the supervision of the Ministry of Education Institute of Special Education of the Deaf directly. 3 - subject teachers to training courses and a variety of continuing to help them develop their potential and knowledge to identify the methods of teaching the hearing-impaired students and the best methods of communication with them.